Optimization Of 3D Printing Of Shape Memory Polymer - Gun, Yong Yin (Universiti Sains Malaysia, 2022)
3D printing is a popular technology in current manufacturing environment since it allows flexible fabrication of complicated product design at a reasonable price. It is an addictive manufacturing process which construct things by layering melted filament. Shape Memory Effect (SME) is a property of Shape Memory Polymer (SMP) where it was able to remember their primary shape, maintaining a secondary shape after being exposed to a strain change, and then returning to the primary shape when external stimulation is applied. In recent years, SMP is one of the widely discussed topics under the 3D printing research field. In this paper, the SME of 3D printed polymer with 75% polylactic acid (PLA) and 25% thermoplastic-urethane (TPU) was investigated. The cycle time for the specimen to return to its primary shape after heated was recorded and the results showed that the most significant factors affecting the SME were the printing temperature and layer height. The tensile test showed that layer height is the most significant factor affecting the responses. Therefore, as suggestions for future work, infill density can be used to replace the printing speed to study the potential of SMP.